Friday Sermon, Power Politics, and Nation-State: A Critical Discourse Analysis of the 2016 Sermon by the FPI Imam - Hatta Raharja; Ibnu Burdah; Hisyam Zaini (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study examines the issue of ownership of the Friday sermon between the government and religious authorities by analyzing the Friday sermon delivered by Muhammad Rizieq Shihab in the context of the 212 Movement for the Defense of Islam in Indonesia. The study is based on the assumption that Friday sermons do not merely serve a didactic and ritualistic function but can also become a form of religious-political discourse that produces legitimacy, frames conflict, and shapes collective attitudes. The study aims to uncover the dominant narrative in the sermon, analyze manifestations of the politicization of the pulpit, and elucidate the role of authority in the production of the sermon’s meaning and its social impact. The study employs a qualitative, descriptive, and analytical methodology, drawing on Norman Fairclough’s critical discourse analysis, Pierre Bourdieu’s concept of symbolic power, and Tahera Qutbuddin’s study on the function of Arabic oratory. The analysis is conducted by describing the textual structure, interpreting discursive practices, and situating the sermon within its social and political context. The study concludes that the sermon constructs a religious-political narrative that frames the defense of the Qur’an, the enforcement of the law, and collective participation as religious and moral obligations. Signs of politicization also emerged in the selection and arrangement of verses, the repetition of religious and legal terminology, and the establishment of contrasts between God’s rule and human rule and between the Qur’anic text and the constitutional text. The study demonstrates that, in this context, the pulpit is not under the absolute control of the government or religious authorities; rather, it is a space where legitimacy is contested, where the legal authority of the state, the symbolic authority of the preacher, and the collective response of the congregation intersect.